Serum testosterone and prostate cancer in men with germline BRCA1/2 pathogenic variants - Alexander Dias; Mark N. Brook; Elizabeth K. Bancroft; Elizabeth C. Page; Anthony Chamberlain; Sibel Saya; Jan Amin; Christos Mikropoulos; Natalie Taylor; Kathryn Myhill; Sarah Thomas; Edward Saunders; et al. (BJUI Compass, 2023)
Abstract Objectives The relation of serum androgens and the development of prostate cancer (PCa) is subject of debate. Lower total testosterone (TT) levels have been associated with increased PCa detection and worse pathological features after treatment. However, data from the Reduction by Dutasteride of Prostate Cancer Events (REDUCE) and Prostate Cancer Prevention (PCPT) trial groups indicate no association. The aim of this study is to investigate the association of serum androgen levels and PCa detection in a prospective screening study of men at higher genetic risk of aggressive PCa due to BRCA1/2 pathogenic variants (PVs), the IMPACT study. Methods Men enrolled in the IMPACT study provided serum samples during regular visits. Hormonal levels were calculated using immunoassays. Free testosterone (FT) was calculated from TT and sex hormone binding globulin (SHBG) using the Sodergard mass equation. Age, body mass index (BMI), prostate‐specific antigen (PSA) and hormonal concentrations were compared between genetic cohorts. We also explored associations between age and TT, SHBG, FT and PCa, in the whole subset and stratified by BRCA1/2 PVs status. Results A total of 777 participants in the IMPACT study had TT and SHBG measurements in serum samples at annual visits, giving 3940 prospective androgen levels, from 266 BRCA1 PVs carriers, 313 BRCA2 PVs carriers and 198 non‐carriers. The median number of visits per patient was 5. There was no difference in TT, SHBG and FT between carriers and non‐carriers. In a univariate analysis, androgen levels were not associated with PCa. In the analysis stratified by carrier status, no significant association was found between hormonal levels and PCa in non‐carriers, BRCA1 or BRCA2 PVs carriers. Conclusions Male BRCA1/2 PVs carriers have a similar androgen profile to non‐carriers. Hormonal levels were not associated with PCa in men with and without BRCA1/2 PVs. Mechanisms related to the particularly aggressive phenotype of PCa in BRCA2 PVs carriers may therefore not be linked with circulating hormonal levels.